A method for purifying bisphenol a by fractional melt crystallization

CN122977937APending Publication Date: 2026-10-27QINGDAO GAOYUNKE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285605.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

针对现有DABPA提纯工艺无法适配88~90%中低纯度双酚A双烯丙基醚原料、超高纯度提纯上限低、高温易聚合、溶剂三废量大、提纯副产物无法利用、物料浪费严重、存在工业废液排放的技术缺陷,本发明提供一种采用分级熔融结晶技术提纯二烯丙基双酚A的方法,基于88~90%纯度醚原料制备的特定组分DABPA粗品,采用两级熔融结晶+梯度发汗耦合提纯技术,低温无溶剂深度脱除杂质,稳定制备HPLC纯度97%以上的超高纯度低粘度DABPA成品;同时对提纯产生的母液、汗液进行专属资源化利用,彻底摒弃传统废液排放与无效回流工艺,实现全物料资源化、零三废绿色生产

Benefits of technology

1、突破原料限制,超高精度提纯:本发明适配工业常规88~90%纯度双酚A双烯丙基醚原料,无需使用高纯度醚原料,通过双级分级结晶+梯度发汗耦合技术,精准、彻底脱除结构相近的单烯丙基副产物、未重排醚类及低聚物杂质,产品HPLC纯度稳定≥97%,彻底突破传统工艺92~93%的提纯上限,解决了行业低品级原料难以制备超高纯DABPA的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977937A_ABST
    Figure CN122977937A_ABST
Patent Text Reader

Abstract

The application discloses a method for purifying diallyl bisphenol A by fractional melting crystallization, and belongs to the technical field of high-performance resin monomer purification. Diallyl bisphenol A (DABPA) crude product is obtained by Claisen thermal rearrangement under the protection of argon gas, with bisphenol A diallyl ether with HPLC purity of 88-90% as raw material. The crude product mainly contains DABPA, bisphenol A diallyl ether, monoallyl bisphenol A and oligomer impurities. The solvent-free low-temperature process of two-stage fractional melting crystallization combined with gradient sweating is adopted to remove ether, monoallyl and oligomer impurities, so that the crude product can be purified to HPLC purity of more than 97%. The crystallization mother liquor and the sweating sweat are not returned to the reaction system, but are directly used as bismaleimide resin toughening modifier resources, so that zero industrial three wastes emission is realized. The application overcomes the defects of high-temperature polymerization, solvent three wastes and large material loss in the traditional process, the finished product has a viscosity of less than 400 mPa・s at 50 DEG C, and the energy consumption is low, the purification efficiency is high, and the application is suitable for industrialized production of high-end electronic and aerospace heat-resistant resins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of high-performance organic monomer purification and fine chemical green purification technology, specifically to a method for purifying diallyl bisphenol A using a step-by-step melt crystallization technique.

[0002] Diallyl bisphenol A (DABPA) is a core functional monomer for modified bismaleimide resins, high-temperature resistant epoxy resins, and high-frequency, high-speed copper-clad laminates. The purity, viscosity, and impurity content of the monomer directly determine the crosslinking density, heat resistance, mechanical toughness, and insulating dielectric properties of the downstream resin. Industrial preparation of DABPA commonly employs the Claisen thermal rearrangement process for bisphenol A diallyl ether. However, limited by the purity of the raw material ether, when using conventional 88-90% low-to-medium purity bisphenol A diallyl ether raw materials, the resulting crude product has a high impurity content and is difficult to purify. Conventional processes cannot achieve high-purity preparation, necessitating a new, high-precision, green, and waste-free purification process. Background Technology

[0003] The current mainstream industrial process for preparing DABPA involves inert-protected thermal rearrangement of bisphenol A diallyl ether to obtain crude DABPA. Conventional industrial raw materials typically use bisphenol A diallyl ether with an HPLC purity of 88-90%. After thermal rearrangement, the crude DABPA composition is fixed as follows: 80-85% DABPA (main product), 5-8% unrearranged bisphenol A diallyl ether, 5-8% monoallyl bisphenol A byproduct, and 4-6% thermally polymerized oligomer impurities. The crude product has a melting point of approximately 20°C and a viscosity as high as 900 mPa·s at 50°C. Impurity enrichment leads to poor flowability, uneven curing and cross-linking, and poor dielectric properties in the crude product. Conventional purification processes cannot achieve deep impurity removal, making it difficult to prepare ultra-high purity DABPA (above 97%), which fails to meet the requirements of high-end applications.

[0004] Existing DABPA purification processes have many inherent flaws; high-purity purification cannot simultaneously achieve high purity, high performance, and green, waste-free production. 1. Molecular distillation process: Relying on high temperature and high vacuum conditions of 220-250℃, the allyl double bonds of DABPA are prone to high-temperature self-polymerization to generate new colloidal impurities, resulting in a darker product color and limited viscosity optimization. For crude products prepared from ether raw materials with a purity of 88-90%, structurally similar monoallylic impurities and ether impurities cannot be effectively separated, and the highest product purity is only 92-93%, which cannot break through the 97% high purity threshold. Moreover, the equipment investment is large, the energy consumption is high, and the material yield is only 75-82%. Most of the separated miscellaneous fractions are discarded as industrial waste liquid, resulting in material waste and pressure on solid and liquid waste treatment.

[0005] 2. Ordinary single-stage cooling crystallization process: There is no sweating impurity stripping process, the crystals encapsulate a large number of impurities, the purification limit is extremely low, the highest purity for low-purity crude products is only 90%, the viscosity improvement effect is poor, the batch stability is insufficient, and it cannot meet the requirements of ultra-high purity products at all.

[0006] 3. Traditional solvent recrystallization process: It consumes a lot of organic solvents, causes serious waste emissions, leaves solvent residues in the product, and results in high dissolution loss and low yield of the target product. Due to the limitations of solvent selectivity, it has a weak ability to separate monoallylic byproducts with highly similar structures, and the highest purification limit is only about 92%, which cannot achieve ultra-high purity purification of 97%. The economic efficiency and product performance cannot meet the standards.

[0007] 4. Conventional melt crystallization process: This process only uses single-stage crystallization or non-sweat crystallization mode, which does not completely remove impurities. It has poor purification effect on low-purity DABPA crude products. At the same time, the mother liquor and sweat produced during purification are mostly directly discarded or simply refluxed for repeated reactions. The highest purification limit is only about 93%, which has always failed to solve the technical bottleneck of high-purity diallyl bisphenol A in the industry.

[0008] Currently, the industry has never targeted the resource utilization of impurity-rich sweat and mother liquor generated during crystallization and purification, resulting in a large waste of functional materials and pollution. However, the main impurity components in diallyl bisphenol A products are bisphenol A diallyl ether, monoallyl bisphenol A, and trace allyl oligomers, all of which contain active allyl functional groups. These are excellent toughening and modifying components for bismaleimide resins. The resin crosslinking network can be optimized through the olefin reaction and diene addition reaction between allyl and maleimide groups, thereby improving the toughness and impact resistance of BMI resins. Therefore, developing a purification process that is adaptable to low-temperature solvent-free processes, can stably prepare ultra-high purity DABPA of over 97%, and achieves full material resource utilization has significant technological innovation value and promising prospects for industrial application. Summary of the Invention

[0009] The technical problem to be solved by the present invention To address the shortcomings of existing DABPA purification processes, such as inability to adapt to 88-90% purity bisphenol A diallyl ether raw materials, low upper limit of ultra-high purity purification, easy polymerization at high temperatures, large amounts of solvent waste, unusable purification byproducts, serious material waste, and industrial wastewater discharge, this invention provides a method for purifying diallyl bisphenol A using a staged melt crystallization technique. Based on crude DABPA of a specific component prepared from 88-90% purity ether raw materials, a two-stage melt crystallization + gradient sweating coupled purification technology is used to deeply remove impurities at low temperatures and without solvents, stably preparing ultra-high purity, low viscosity DABPA finished products with HPLC purity of over 97%. Simultaneously, the mother liquor and sweat generated during purification are specifically utilized for resource recovery, completely eliminating traditional wastewater discharge and ineffective reflux processes, achieving full material resource utilization and zero-waste green production.

[0010] Technical solution A method for purifying diallyl bisphenol A using a step-by-step melt crystallization technique, characterized by comprising the following steps: S1. Raw material pretreatment and crude product preparation: Bisphenol A diallyl ether with an HPLC purity of 88-90% was selected as the reaction raw material. Argon gas was introduced to maintain a slightly positive pressure inert protective atmosphere. The oxygen content of the system was ≤100ppm. The temperature was raised to 185-205℃ and held for 2-4 hours to carry out the Claisen thermal rearrangement reaction. After natural cooling, crude diallyl bisphenol A was obtained. The crude product had a melting point of about 20℃ and its components by mass percentage included: 80-85% diallyl bisphenol A, 5-8% bisphenol A diallyl ether, 5-8% monoallyl bisphenol A, and 4-6% oligomer impurities. The obtained crude product was heated to 40-55℃ to completely melt it. It was then precisely filtered to remove trace amounts of solid coke and macromolecular polymer impurities to obtain a homogeneous molten crude material. S2, Primary Melting and Crystallization: The homogeneous molten coarse material is fed into a shell-and-tube type stirless static melting and crystallizing apparatus under argon micro-positive pressure protection throughout the process; the temperature is lowered to 15-28℃ at a slow programmed cooling rate of 0.05-0.2℃ / min, and then kept at a constant temperature for 2-8 hours for crystallization. Taking advantage of the difference in melting point and crystallization rate between the target product and impurities, high-regularity DABPA is preferentially crystallized and precipitated, while bisphenol A dielyl ether, monoallyl byproducts, and oligomer impurities are enriched in large quantities in the uncrystallized mother liquor; after crystallization, the primary crystallization mother liquor is collected separately. S3. Primary gradient sweating purification: After crystallization, the temperature is increased to 28-38℃ at a rate of 0.05-0.3℃ / min and sweated at a constant temperature for 1-5 hours; the low melting point impurity phase wrapped in the crystal surface and micropores preferentially melts and seeps out, completely removing the enriched impurities carried on the crystal surface, and collecting the primary sweating liquid separately. S4. Primary Crystal Melting: After sweating, continue to heat to 40-55℃ to completely melt all the high-purity crystals in the crystallizer and obtain the primary purified material. S5, Secondary Melting Crystallization: The material purified in the primary stage is fed into the secondary static melting crystallizer, which is kept under argon inert protection. The temperature is reduced to 18-30°C at a rate of 0.05-0.2°C / min, and the material is kept at a constant temperature for 2-7 hours to remove trace amounts of residual impurities and achieve high-precision purification. The secondary crystallization mother liquor is collected separately after crystallization is completed. S6. Secondary gradient sweating purification: After the secondary crystallization is completed, the temperature is increased to 30-40℃ at a rate of 0.05-0.3℃ / min, and the temperature is kept constant for 1-4 hours to deeply peel off the trace impurities wrapped in the micropores of the crystals, completely remove trace structurally similar impurities, and collect the secondary sweating liquid separately. S7. Finished product melting and discharge: After sweating, the temperature is raised to 42-55℃ to completely melt the secondary high-purity crystals. After filtration, ultra-high purity diallyl bisphenol A product is obtained. S8. Purification and Resource Utilization of By-products: The collected primary crystallization mother liquor, secondary crystallization mother liquor, primary sweating liquid, and secondary sweating liquid are uniformly mixed and collected to obtain an allyl mixture enriched with impurities. The main components of the mixture are bisphenol A dielyl ether, monoallyl bisphenol A, and trace allyl oligomers, containing a large number of active allyl functional groups. This part of the material is not refluxed to the reactor, not refluxed to the crystallization equipment, and is not discharged externally. It is directly used as a toughening modifier for bismaleimide resin and used in the copolymerization modification production of BMI resin.

[0011] Preferably, the crude product prepared from 88-90% pure bisphenol A dielyl ether raw material is purified by two-stage fractional melt crystallization and gradient perspiration. The high-purity DABPA product has a stable HPLC purity of ≥97%, and the kinematic viscosity at 50°C decreases from 900 mPa·s in the crude product to 400 mPa·s and below.

[0012] Preferably, the maximum operating temperature throughout the graded melt crystallization process is ≤55℃, with no organic solvents involved and inert gas protection throughout, completely eliminating product oxidation and thermal polymerization side reactions.

[0013] Explanation of core process principles This invention employs a low-temperature gradient melting crystallization + two-stage sweating deep stripping mechanism to achieve ultra-high precision separation of crude DABPA prepared from 88-90% low-purity ether raw materials, utilizing the significant differences in melting point, crystallinity, and crystallization rate between DABPA and various impurities: DABPA has a higher melting point, symmetrical molecular structure, and excellent crystallinity, allowing for preferential and orderly crystallization; bisphenol A dielyl ether, monoallyl bisphenol A, and allyl oligomer impurities have lower melting points and stronger crystallinity disorder, mainly remaining in the crystallization mother liquor, while trace impurities are physically encapsulated on the crystal surface and within micropores. Initial enrichment and separation of impurities are achieved through two-stage gradient cooling crystallization, followed by two-stage slow gradient heating sweating, allowing the low-melting-point impurity phases to melt and seep out layer by layer, completely removing trace structurally similar impurities that cannot be removed by conventional processes, ultimately achieving the preparation of ultra-high purity DABPA products from low-purity raw materials.

[0014] The key innovations of this invention are: First, it breaks through the upper limit of traditional purification processes. Using industrially common ethers with a purity of 88-90% as raw materials, it can stably prepare ultra-high purity DABPA of over 97% without the need for pre-refining raw materials, significantly reducing raw material procurement costs. Second, it achieves zero-waste resource utilization of purification byproducts. Bisphenol A dielyl ether and monoallyl bisphenol A enriched in sweat and mother liquor both contain active allyl structures, which can undergo ene reactions and Diels-Alder addition reactions with bismaleimide monomers. This effectively regulates the crosslinking network structure of BMI resin, reduces the resin crosslinking density, releases molecular chain movement space, and significantly improves the toughness, impact resistance, and processing fluidity of BMI resin. It is a high-quality toughening and modifying component for high-performance BMI resin and has extremely high resource value.

[0015] This invention completely eliminates the drawbacks of traditional processes, such as "accumulation of impurities due to mother liquor reflux, environmental pollution from waste liquid discharge, and waste of functional materials," and achieves ultra-high purity purification of the main product and full resource utilization of by-products, thus achieving zero industrial waste emissions.

[0016] This method not only significantly improves the product quality of diallyl bisphenol A, but also effectively avoids the side reactions that are prone to occur in traditional heat-sensitive substances under high-temperature or organic solvent environments through a low-temperature solvent-free process. The inert gas protection throughout the process further ensures the product's light color and high stability, meeting the stringent purity requirements of high-end electronic materials. Simultaneously, the closed-loop utilization of byproducts significantly reduces production costs and environmental impact, providing a green and efficient raw material solution for the bismaleimide resin industry, with significant industrial application prospects and economic value. Beneficial effects 1. Breaking through raw material limitations and achieving ultra-high precision purification: This invention is compatible with industrially available 88-90% purity bisphenol A diallyl ether raw materials, eliminating the need for high-purity ether raw materials. Through a two-stage fractional crystallization + gradient sweating coupling technology, it accurately and thoroughly removes structurally similar monoallyl byproducts, unrearranged ethers, and oligomer impurities. The product has a stable HPLC purity of ≥97%, completely breaking through the traditional process's purification limit of 92-93%, and solving the technical problem of preparing ultra-high purity DABPA from low-grade raw materials in the industry.

[0017] 2. Significantly optimized product performance: Effectively removes macromolecular oligomers and trace impurities. The viscosity of the finished product at 50°C is reduced from 900 mPa·s in the crude product to below 400 mPa·s. The product has a regular molecular structure, uniform cross-linking, excellent flowability, and extremely strong batch stability, which can meet the stringent requirements for ultra-high purity DABPA in aerospace, high-end electronic packaging, high-frequency and high-speed copper-clad laminates and other fields.

[0018] 3. Low temperature and solvent-free, superior product quality: The maximum operating temperature throughout the process is ≤55℃, which completely eliminates the problems of high-temperature thermal polymerization and cross-linking of allyl double bonds, and no new impurities are generated; no organic solvents are involved, no solvent residues, and no organic waste. The purity, color, and stability of the product are significantly better than those of products produced by molecular distillation and solvent recrystallization.

[0019] 4. Pioneering zero-waste, three-waste, and full-resource utilization process: In this invention, all crystallization mother liquor and sweating liquid do not flow back into the production system or are discharged externally. Instead, they are all used as functional raw materials for toughening and modifying bismaleimide resin, turning waste into treasure. This completely solves the industry problems of material waste and waste liquid and solid waste discharge in traditional purification processes, achieving zero-waste, three-waste, and full-material resource utilization in industrial production, with significant green and environmental protection advantages.

[0020] 5. Excellent process economy and suitable for industrialization: No high vacuum and high temperature equipment is required, and the equipment investment and operating energy consumption are far lower than those of molecular distillation process; there is no solvent recovery or waste treatment cost; high value-added ultra-high purity products can be prepared from low purity ether raw materials, while by-products can be utilized to increase value, greatly improving the overall production economic benefits, and is suitable for large-scale industrial continuous production.

[0021] 6. Strong batch stability: The dual-gradient sweating process deeply removes trace impurities from the surface and pores of the crystals, avoiding the problem of residual impurities and fluctuations in ordinary crystallization processes. The purity and viscosity of the ultra-high purity product are uniform and stable, and it has strong industrial adaptability. Detailed Implementation

[0022] The present invention will be further described in detail below with reference to specific embodiments. All test methods adopt the HPLC area normalization method, with argon gas micro-positive pressure protection throughout the process. The melting point of the crude product is 20℃, and the viscosity of the crude product at 50℃ is 900mPa·s.

[0023] Example 1 S1. Raw material pretreatment: Bisphenol A diallyl ether with an HPLC purity of 89.0% was selected and thermally rearranged at 195℃ for 3 hours under argon protection to obtain crude DABPA; crude product composition: DABPA 84.0%, bisphenol A diallyl ether 6.5%, monoallyl bisphenol A 5.5%, oligomers 4.0%; the crude product was heated to 50℃ to completely melt and then precisely filtered to remove solid impurities; S2, Primary crystallization: Cooling rate 0.1℃ / min, cool to 22℃, crystallize at constant temperature for 4h, and collect the mother liquor of primary crystallization; S3, Level 1 sweating: The temperature rises at a rate of 0.15℃ / min, reaches 33℃, and is kept at a constant temperature for 2.5 hours. The sweat from Level 1 sweating is then collected. S4. Primary melting: Heat to 50℃ and melt completely to obtain primary purified material; S5, Secondary crystallization: Cooling rate 0.1℃ / min, cool to 24℃, crystallize at constant temperature for 3.5h, and collect the secondary crystallization mother liquor; S6. Secondary sweating: The heating rate is 0.15℃ / min, the temperature is raised to 35℃, and the sweating is kept at a constant temperature for 2 hours. The sweat from the secondary sweating is then collected. S7. Finished product melting and discharge: The temperature is raised to 52℃ and completely melted. The ultra-high purity material is sent to the finished product storage tank. S8. By-product resource utilization: The primary mother liquor, primary sweat, secondary mother liquor and secondary sweat are mixed and collected. The main components of the resulting mixture are bisphenol A dielyl ether, monoallyl bisphenol A and trace oligomers, all of which are directly used for toughening and modification of bismaleimide resin. Test results: The finished product DABPA has a purity of 97.5%, a viscosity of 385 mPa·s at 50℃, and an overall yield of 80.6%; the by-product modified BMI resin has an increased fracture toughness of 18.2%, and no industrial waste is generated.

[0024] Example 2 S1. Raw material pretreatment: Bisphenol A diallyl ether with an HPLC purity of 88.2% was selected and thermally rearranged at 190℃ for 3.5h under argon protection. The resulting crude DABPA composition was: DABPA 82.8%, bisphenol A diallyl ether 7.2%, monoallyl bisphenol A 6.0%, and oligomers 4.0%. The mixture was then heated to 50℃ and filtered through a melt filter. S2, Primary crystallization: Cooling rate 0.08℃ / min, cool to 20℃, crystallize at constant temperature for 5h, and collect the primary mother liquor; S3, Level 1 Sweating: Raise the temperature to 31℃, maintain the temperature for 3 hours to induce sweating, and collect the Level 1 sweat. S4. Primary melting yields intermediate materials; S5, Secondary crystallization: Cool to 21℃, crystallize at a constant temperature for 4 hours, and collect the secondary mother liquor; S6. Secondary sweating: Raise the temperature to 33℃, maintain the temperature for 2.5 hours, and collect the secondary sweat. S7. Melt and discharge to obtain ultra-high purity finished product; S8. By-product resource utilization: All mother liquor and sweat are collected in a unified manner and used entirely for toughening and modification of bismaleimide resin; Test results: The finished product DABPA has a purity of 97.1%, a viscosity of 392 mPa·s at 50℃, and a comprehensive yield of 81.3%; no industrial waste is generated, and the resource utilization of by-products is excellent.

[0025] Example 3 S1. Raw material pretreatment: Bisphenol A diallyl ether with an HPLC purity of 89.8% was selected and thermally rearranged at 200℃ for 2.5h under argon protection. The resulting crude DABPA composition was: DABPA 84.5%, bisphenol A diallyl ether 5.8%, monoallyl bisphenol A 5.2%, and oligomers 4.5%. The mixture was then heated to 50℃ and filtered through a melt filter. The subsequent crystallization and sweating process parameters are the same as in Example 1; Test results: The finished product DABPA has a purity of 97.8%, a viscosity of 378 mPa·s at 50℃, and a comprehensive yield of 79.8%. The product has high purity, low viscosity, and excellent batch performance.

[0026] Comparative Example To fully demonstrate the inventiveness, advancement, and beneficial effects of this invention, parallel comparative experiments were conducted using the exact same batch of crude DABPA (initial purity 84.0%, viscosity at 50°C 900 mPa·s, melting point 20°C) as in Example 1 of this invention. The comparative examples maintained complete operational steps and used industry-standard optimal process parameters, as detailed below: Comparative Example 1: Conventional single-stage cooling crystallization process (no grading, no sweating) Complete operating steps: Heat the same batch of crude DABPA to 50°C until completely melted, and send it into a static crystallizer under argon protection; cool down to 22°C at a rate of 0.1°C / min, and let it stand at a constant temperature for 4 hours to crystallize; after crystallization, directly discharge all mother liquor, without heating and sweating or impurity stripping processes; continue to heat to 50°C to melt all the crystals and discharge the material to complete the purification.

[0027] Test results: The purity of the purified DABPA product is only 88.9%, which cannot break through the 90% purity threshold, let alone reach the 97% ultra-high purity standard; the kinematic viscosity at 50℃ is 715 mPa·s, and the viscosity decrease is minimal.

[0028] Comparative Example 2: Traditional Solvent Recrystallization Process Complete operating steps: Take equal mass of the same batch of crude DABPA, and dissolve the crude product completely in a toluene-anhydrous ethanol mixed solvent (volume ratio 3:1) according to the optimal industrial standard ratio. Heat to 55°C and stir thoroughly to dissolve, preparing a saturated solution. After removing impurities by standing at a constant temperature, slowly cool to 10°C at 0.1°C / min and let it stand at low temperature for 6 hours to crystallize. Filter and collect the solid crystals, and wash the residual mother liquor on the crystal surface with a small amount of cold mixed solvent. Heat the obtained solid to melt, and remove all solvent under vacuum to obtain the solvent recrystallization purified product.

[0029] Test results: The highest purity of the purified DABPA product is only 91.5%, with an insurmountable purification limit, and it cannot reach the ultra-high purity index of 97%; the viscosity at 50℃ is 605 mPa·s; the overall material yield is only 68.3%; and trace amounts of organic solvent residue are detected in the product.

[0030] Comparative Example 3: Single-stage melt crystallization process without sweating Complete operating steps: Take crude DABPA from the same batch, heat it to 50℃ to completely melt it, and then filter it precisely to remove impurities; under argon protection, send it into a primary melt crystallizer, cool it to 22℃ at a rate of 0.1℃ / min, and crystallize it at a constant temperature for 4 hours to fully enrich the impurities; after crystallization, completely discharge the high-impurity mother liquor, cancel the gradient sweating and heating stripping step, and directly heat it to 50℃ to melt all the crystals in the crystallizer and discharge the purified product.

[0031] Test results: The purity of the purified DABPA product was only 87.8%, indicating extremely poor purification effect; the viscosity at 50℃ was 675 mPa·s, indicating high levels of residual impurities.

[0032] Comparative Example 4: Traditional Molecular Distillation Process Complete operating steps: Take crude DABPA from the same batch and preheat it to 60℃ to completely melt it; send it into an industrial-grade short-path molecular distillation apparatus, set the evaporation temperature to 230℃, the system vacuum degree to 0.5Pa, the scraper speed to 300r / min, and the material residence time to 90s; nitrogen gas is introduced throughout the process for protection, light component impurities are discharged from the distillation end, and heavy component products are collected from the bottom of the vessel to complete the high-temperature purification.

[0033] Test results: The highest purity of the purified DABPA product was only 92.8%, which could not break through the 97% ultra-high purity threshold; the viscosity at 50℃ was 580 mPa·s; the overall material yield was only 76.3%; the product color was dark, and there were trace amounts of colloidal polymer impurities in the product, and a large amount of trace amounts of colloidal polymer impurities were found in the residual mother liquor. Attached Figure Description Figure 1 This is a schematic diagram of the process flow for a method of purifying diallyl bisphenol A using a graded melt crystallization technique according to the present invention.

Claims

1. A method for purifying diallyl bisphenol A using a staged melt crystallization technique, characterized in that, Includes the following steps: S1. Raw material pretreatment and crude product preparation: Bisphenol A diallyl ether with an HPLC purity of 88-90% was selected as raw material. Under a slightly positive pressure inert atmosphere of argon, the Claisen thermal rearrangement reaction was carried out at 185-205℃ for 2-4 hours to obtain crude diallyl bisphenol A. The crude product has a melting point of about 20℃ and its components by mass percentage include: 80-85% diallyl bisphenol A, 5-8% bisphenol A diallyl ether, 5-8% monoallyl bisphenol A, and 4-6% oligomer impurities. The crude product was heated to 40-55℃ and completely melted. After filtration to remove impurities, a homogeneous molten crude product was obtained. S2, Primary Melting and Crystallization: The molten coarse material is fed into a static melting and crystallizing apparatus under argon protection throughout the process, with the oxygen content of the system ≤100ppm. The temperature is reduced to 15-28℃ at a rate of 0.05-0.2℃ / min, and crystallized at a constant temperature for 2-8 hours. The primary mother liquor enriched with impurities is then discharged. S3. Primary gradient perspiration purification: Heat to 28-38℃ at a rate of 0.05-0.3℃ / min, maintain the temperature for 1-5 hours to remove impurities from the crystal surface, and collect the primary perspiration. S4. Primary crystal melting: Heat to 40-55℃ to completely melt the primary crystals and obtain the purified material. S5, Secondary Melting Crystallization: The material purified in the primary stage is fed into the secondary static melting crystallizer, and cooled to 18-30℃ at a rate of 0.05-0.2℃ / min under argon protection. The crystallization is carried out at a constant temperature for 2-7 hours, and the secondary mother liquor is discharged. S6. Secondary gradient perspiration purification: Heat to 30-40℃ at a rate of 0.05-0.3℃ / min, maintain the temperature for 1-4 hours to deeply remove trace impurities from crystal pores, and collect secondary perspiration. S7. Finished product melting and discharge: Heat to 42-55℃ and completely melt the secondary high-purity crystals to obtain high-purity diallyl bisphenol A finished product. S8. By-product resource utilization: The primary mother liquor, primary sweat, secondary mother liquor, and secondary sweat are collected in a unified manner. The main components of the materials are bisphenol A dielyl ether, monoallyl bisphenol A, and oligomers, containing active allyl functional groups. This part of the material is not returned to the production system or discharged to the outside. It is all utilized as a toughening modifier for bismaleimide resin.

2. The method for purifying diallyl bisphenol A using a staged melt crystallization technique according to claim 1, characterized in that, The static melting crystallizer is a shell-and-tube type, stirless static crystallizer that achieves programmed heating and cooling through closed-loop precise temperature control of the hot and cold medium.

3. The method for purifying diallyl bisphenol A using a staged melt crystallization technique according to claim 1, characterized in that, The crude product prepared from 88-90% pure bisphenol A diallyl ether raw material, after purification, has an HPLC purity of ≥97% for the finished product diallyl bisphenol A, and its viscosity at 50℃ decreases from 900 mPa·s in the crude product to 400 mPa·s and below.

4. The method for purifying diallyl bisphenol A using a staged melt crystallization technique according to claim 1, characterized in that, The maximum operating temperature throughout the entire process is ≤55℃, with no organic solvents involved, and the entire process is protected by inert gas to prevent product oxidation and thermal polymerization.

5. The method for purifying diallyl bisphenol A using a staged melt crystallization technique according to claim 1, characterized in that, All mother liquor and sweat produced during purification are used for toughening and modification of bismaleimide resin, achieving zero industrial waste and full material resource utilization.